Evaluation of the burden of migraine on the partner’s lifestyle - E. Fernández-Bermejo; Á. Planchuelo-Gómez; S. Quintas; A. Gonzalez-Martinez; D. García-Azorín; Á. Sierra-Mencía; Á.L. Guerrero; S. Santos-Lasaosa; M. Pilar Navarro-Pérez; N. González-García; J. Díaz-de-Terán; A.B. Gago-Veiga (Neurología (English Edition))
Background: Despite the number of research studies regarding the individual burden of migraine, few studies have examined its impact on the patients’ partners. We aim to assess migraine effects on the patients’ partners on sentimental relationship, children relationship, friendship, and work, as well as the caregiver burden, anxiety and/or depression. Methods: A cross-sectional observational study was conducted through an online survey of partners of patients with migraine followed-up in 5 Headache Units. Questions about the 4 areas of interest and 2 scales (Hospital Anxiety and Depression Scale and Zarit scale) were included. Scores were compared against the population prevalence. Results: One hundred and fifty-five answers were analysed. Among the patient’s partners 135/155 (87.1%) were men, with a mean age of 45.6 ± 10.1 years. Migraine’s main effects on partners were observed in the sentimental relationship and items concerning children and friendships, with a minor impact at work. Partners showed a moderate burden (12/155 = 7.7% [4.1%–13.1%]), and a higher moderate-severe anxiety rate (23/155 = 14.8% [9.6%–21.4%]), and similar depression rate (5/155 = 3.2% [1.1%–7.3%]) compared to the National Health Survey. Conclusions: The burden of migraine impacts the partners’ personal relationship, childcare, friendship and work. Moreover, certain migraine partners showed a moderate burden according to Zarit scale and higher anxiety levels than the Spanish population. Resumen: Introducción y objetivos: Diversos estudios han evaluado la sobrecarga individual de la migraña, sin embargo, pocos estudios han examinado su impacto en las parejas de los pacientes. Nuestro objetivo es evaluar los efectos de la migraña en las parejas de los pacientes sobre la relación sentimental, la relación con los hijos, la amistad y el trabajo, así como la sobrecarga del cuidador, la ansiedad y/o la depresión. Material y métodos: Se realizó un estudio observacional transversal a través de un cuestionario en línea a las parejas de pacientes con migraña seguidos en cinco Unidades de Cefalea. Se incluyeron preguntas sobre las cuatro áreas de interés y dos escalas (Escala de Ansiedad y Depresión Hospitalaria y escala de Zarit). Las puntuaciones se compararon con la prevalencia de la población según la Encuesta Nacional de Salud. Resultados: Se analizaron ciento cincuenta y cinco respuestas. Las parejas de los pacientes con migraña fueron 135/155 (87.1%) hombres, edad media de 45.6 ± 10.1 years; Los principales efectos de la migraña en la pareja se observaron en la relación sentimental y en los ítems relativos a los hijos y las amistades, con menor impacto en el trabajo. Las parejas mostraron una carga moderada (12/155 = 7,7%[4,1%-13,1%]), y una tasa de ansiedad moderada-grave más alta (23/155 = 14,8%[9,6%-21,4%]) y una tasa de depresión similar (5/155 = 3,2%[1,1%-7,3%]) respecto a la población española. Conclusiones: La carga de la migraña tiene un impacto en la relación personal de la pareja, el cuidado de los hijos, la amistad y el trabajo. Además, algunos cuidadores de pacientes con migraña presentan una carga moderada y niveles de ansiedad más altos que la población española.